Sosialisasi Implementasi Manajemen Waktu Pada Siswa SDN 1 Puunokullo - Hartati Hartati; Fransischa Apryeni; Ija Rianti; Muh. Febriansyah Karlis; Muh. Ibra Julianto; Eka Aprilia; Reski Reski; Feniliana Feniliana; Keysa Keysa; Bunga Aulia; Isman.H (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Time management is an essential skill that should be possessed by every individual, including elementary school students. Many students experience difficulties in balancing their study, play, and rest time. This community service activity aims to provide socialization and education regarding the importance of implementing time management among students at SDN 1 Puunokullo. The implementation method was carried out through socialization activities and interactive discussions using visual media, as well as the reward method. The results of the activity showed that students were highly enthusiastic and understood the importance of managing their time in daily activities. Teachers and the school also provided full support for this activity, as it was considered effective in fostering students’ awareness of discipline and responsibility.